2005
DOI: 10.1159/000084023
|View full text |Cite
|
Sign up to set email alerts
|

Combined Electric and Acoustic Stimulation of the Auditory System: Results of a Clinical Study

Abstract: Combined electric and acoustic stimulation (EAS) of the auditory system is a new therapy for patients with severe to profound high- and mid-frequency hearing loss but remaining low-frequency hearing. In a prospective study, 13 patients with low-frequency hearing of better than 60 dB below 1 kHz were implanted with a MED-EL COMBI 40+ cochlear implant. Pure tone thresholds as well as monosyllabic word scores and Hochmair-Schulz-Moser sentences in quiet and in noise were measured with hearing aids, cochlear impla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
224
0
5

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(250 citation statements)
references
References 43 publications
20
224
0
5
Order By: Relevance
“…Moreover, the patient indicated that the implant was very valuable in everyday situations. The improvement in performance when electric and acoustic stimulation were combined is consistent with previous reports for patients with residual low-frequency hearing ipsilateral and/or contralateral to an ear with a cochlear implant (e.g., Ching et al 2004;Gantz et al 2005;Kiefer et al 2005;Kong et al 2005;v. Ilberg et al 1999).…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, the patient indicated that the implant was very valuable in everyday situations. The improvement in performance when electric and acoustic stimulation were combined is consistent with previous reports for patients with residual low-frequency hearing ipsilateral and/or contralateral to an ear with a cochlear implant (e.g., Ching et al 2004;Gantz et al 2005;Kiefer et al 2005;Kong et al 2005;v. Ilberg et al 1999).…”
Section: Discussionsupporting
confidence: 89%
“…Gstoettner et al (2004) reported speech results for one patient implanted with a 22mm electrode who improved from 38%-recognition of monosyllables in the acoustic-only mode to 90% with the addition of electric stimulation. Kiefer et al (2005) reported monosyllabic word understanding a group of 11 patients with preserved residual hearing. Mean acoustic-alone scores were 7%-correct, and the addition of electric stimulation increased this to over 60%, with several patients showing scores increasing to over 75%.…”
Section: A+e Results For Speech Presented In Quietmentioning
confidence: 99%
“…Gstoettner et al (2004) described full or at least partial preservation of hearing in 18 of 21 patients using this technique. Kiefer et al (2005) reported that at least partial preservation of hearing was accomplished in 11 out of 13 patients. The mean threshold change for those 11 patients was approximately 15 dB at the lower frequencies, while the remaining 2 patients suffered essentially total losses.…”
Section: Preservation Of Hearing Following Cochlear Implant Surgerymentioning
confidence: 99%
“…(This ability is nonexistent or almost nil with a unilateral implant, as noted before.) Combined EAS also provides a substantial benefit for listening to speech in quiet, in noise, in competition with another talker, or in competition with a multi-talker babble, compared with either electric stimulation only or acoustic stimulation only (e.g., von Ilberg et al, 1999;Kiefer et al, 2002Kiefer et al, , 2005Gantz and Turner, 2003;Wilson et al, 2003;Gstoettner et al, 2004Gstoettner et al, , 2006Gantz et al, 2005Gantz et al, , 2006Kong et al, 2005;James et al, 2006;Gifford et al, 2007;Dorman et al, 2007;Turner et al, this issue). Indeed, in some cases the score for combined EAS is greater than the sum of the scores for the electric-only and acoustic-only conditions.…”
Section: Two Recent Advancesmentioning
confidence: 99%